study

integral sign S (limits 1/x to x) function f(t) ?

if S (1/x to x) function f(t) = S (1 to x) t^3 function f(t)

f(t) = 1/(1+t^2)(1+t^3)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Since the problem provides the information that `int_(1/x)^x f(t) dt = int_1^x t^3f(t) dt` , yields:

`int_1^x t^3f(t) = int_1^x t^3/(1+t^2)(1+t^3) dt`

You should add and subtract 1 such that:

`int_1^x t^3 (t^3+1-1)/(1+t^2)(1+t^3) dt`

Using the linearity of integral yields:

`int_1^x (t^3+1-1)/(1+t^2)(1+t^3) dt = int_1^x (t^3+1)/(1+t^2)(1+t^3) dt - int_1^x (1)/(1+t^2)(1+t^3) dt`

`int_1^x (t^3+1-1)/(1+t^2)(1+t^3) dt = int_1^x 1/(1+t^2) dt- int_1^x (1)/(1+t^2)(1+t^3) dt`

You should use partial fraction decomposition to solve `int_1^x (1)/(1+t^2)(1+t^3) dt`  such that:

`1/(1+t^2)(1+t^3) = (At + B)/(t^2+1) + C/(t+1) + (Dt+E)/(t^2-t+1)`

`1 = (At + B)(t^3+1) + C(t^2+1)(t^2-t+1) + (Dt+E)(t^2+1)(t+1)`

`1 = At^4 + At + Bt^3 + B + Ct^4 - Ct^3 + Ct^2 + Ct^2 - Ct + C + (Dt^3 + Dt + Et^2 + Et)(t+1)`

`1 = At^4 + At + Bt^3 + B + Ct^4 - Ct^3 + Ct^2 + Ct^2 - Ct + C + Dt^4 + Dt^2 + Et^3 + Et^2 + Dt^3 + Dt + Et^2 + Et`

`1 = t^4(A+C+D) + t^3(B - C + E + D) + t^2(2C + D + 2E) + t(A - C + D + E) + B + C`

Equating the coefficients of like powers yields:

`A+C+D = 0`

`B - C + E + D = 0`

`2C + D + 2E = 0`

`A - C + D + E = 0`

`B + C = 1`

`2B+E+D = 1 => 2B+E+D-2A-2D-E = 1 => 2B-2A-D = 1`

`2A+2D+E=0`

`A = 0 => B = 1/4 => C = 1 - 1/4 = 3/4 => D = -3/4=> E = 3/8`

`1/(1+t^2)(1+t^3) = 1/(4(t^2+1)) + 3/(4(t+1))- (3/4)(2t-1)/(t^2-t+1)`

`int_1^x (1)/(1+t^2)(1+t^3) dt = int_1^x 1/(4(t^2+1))dt+ int_1^x 3/(4(t+1)) dt- (3/4) int_1^x (2t-1)/(t^2-t+1) dt`

Using the fundamental theorem of calculus yields:

`int_1^x (1)/(1+t^2)(1+t^3) dt = ((1/4) arctan(t^2+1) + (3/4)ln|t+1| - (3/4)ln(t^2-t+1))|_1^x`

`int_1^x (1)/(1+t^2)(1+t^3) dt = (1/4) (arctan(x^2+1) - arctan 2) + (3/4)(ln|x+1| - ln2) - (3/4)(ln(x^2-x+1))`

`int_1^x (t^3+1-1)/(1+t^2)(1+t^3) dt = (3/4)(arctan(x^2+1) - arctan 2) - (3/4)(ln|x+1| - ln2)+ (3/4)(ln(x^2-x+1))`

Hence, evaluating the given integral yields `int_1^x (t^3+1-1)/(1+t^2)(1+t^3) dt = (3/4)(arctan(x^2+1) - arctan 2) - (3/4)(ln|x+1| - ln2) + (3/4)(ln(x^2-x+1)).`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial